MicroRNA‐425‐5p regulates chemoresistance in colorectal cancer cells via regulation of Programmed Cell Death 10. Issue 2 (9th December 2015) - Zhang, Ye; Hu, Xingqian; Miao, Xiaofei; Zhu, Kuiyu; Cui, Songkui; Meng, Qingyang; Sun, Jialin; Wang, Tong
Abstract: Acquired chemoresistance represents a major obstacle in cancer treatment, the underlying mechanism of which is complex and not well understood. MiR‐425‐5p has been reported to be implicated tumorigenesis in a few cancer types. However, its role in regulating chemoresistance has not been investigated in colorectal cancer (CRC) cells. Microarray analysis was performed in isogenic chemosensitive and chemoresistant HCT116 cell lines to identify differentially expressed miRNAs. miRNA quantitative real‐time PCR was used to detect miR‐425‐5p expression levels between drug resistant and parental cancer cells. MiR‐425‐5p mimic and inhibitor were transfected, followed by CellTiter‐Glo ® assay to examine drug sensitivity in these two cell lines. Western Blot and luciferase assay were performed to investigate the direct target of miR‐425‐5p. Xenograft mouse models were used to examine in vivo function of miR‐425‐5p. Our data showed that expression of miR‐425‐5p was significantly up‐regulated in HCT116‐R compared with parental HCT116 cells. Inhibition of miR‐425‐5p reversed chemoresistance in HCT116‐R cells. Programmed cell death 10 (PDCD10) is the direct target of miR‐425‐5p which is required for the regulatory role of miR‐425‐5p in chemoresistance. MiR‐425‐5p inhibitor sensitized HCT116‐R xenografts to chemo drugs in vivo . Our study demonstrated that miR‐425‐5p regulates chemoresistance of CRC cells by modulating PDCD10 expression level both in vitro and in vivo . MiR‐425‐5p may represent a new therapeutic target for the intervention of CRC.